Relation between retrobulbar circulation and progression of diabetic retinopathy. Issue 5 (1st May 2003) - Dimitrova, G; Kato, S; Yamashita, H; Tamaki, Y; Nagahara, M; Fukushima, H; Kitano, S
Abstract : Aims: To investigate retrobulbar circulatory parameters in type 2 diabetic patients with and without diabetic retinopathy (DR) progression. Methods: This was a prospective cohort study. One eye of 35 diabetic patients with background DR (BDR) were included in the study. Eyes without DR, with proliferative DR, photocoagulation, past surgical procedures, or other ophthalmic disease except BDR and cataract were excluded. The study was masked. Colour Doppler imaging (CDI) was used to measure the retrobulbar circulation at the beginning of the study and after a mean follow up interval of 21 months. Peak systolic velocity (PSV), end diastolic velocity (EDV), and resistivity index (RI) in the central retinal artery and vein and the posterior ciliary artery were measured. Results: 18 patients who developed DR progression showed significantly increased central retinal vein PSV ( 5.6 (3.5–9.1) p = 0.003), EDV ( 3.4 (2.3–4.4) p = 0.04), and RI ( 0.43 (0.20–0.56) p = 0.02) at the final measurement compared to the initial measurement (PSV = 4.6 (3.2–7.0); EDV = 3.0 (2.3–3.7); RI = 0.40 (0.17–0.52)). Circulatory parameters in the central retinal artery and the posterior ciliary artery did not alter significantly after progression of DR. 17 patients were without DR progression and they did not show any significant differences in the measured circulatory parameters on entry compared to the final measurement. Conclusion: The authors suggest that the initial changes in the retrobulbar circulation during DR progression occur in the central retinal vein.